Cellulose nanofiber manufacturing equipment
By setting a tight gap between the cylinder and the pump seat of the high-pressure pump and providing an embedded structure between the pump seat and the pump base, the problem of frequent damage to the high-pressure pump parts is solved, extending the service life of the equipment and reducing replacement costs.
Patent Information
- Application Number
- JP2024119246
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-07-25
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2044-07-25
AI Technical Summary
The high-pressure pump components in the high-pressure homogenizer are frequently damaged due to long-term defibrillation treatment, resulting in high replacement costs.
By providing a tight gap (1 mm or less) between the cylinder and the pump seat of the high-pressure pump and providing an inline structure between the pump seat and the pump base, it reduces mechanical friction and wear.
It extends the service life of high-pressure pumps, reduces the frequency and cost of replacing components, and improves the reliability and efficiency of equipment.
Smart Images

Figure 0007656136000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a cellulose nanofiber production apparatus equipped with a high-pressure homogenizer. [Background technology]
[0002] Nanotechnology, a technique for freely controlling matter in the nanometer range, that is, on the scale of atoms and molecules, is expected to give rise to a variety of convenient new materials and devices. In particular, nano-order fibers (nanofibers) have attracted a great deal of attention because making fibers as thin as possible gives rise to completely new physical properties not found in conventional fibers. It is expected that the application of nanofibers will lead to the realization of purification devices with high-performance filters that do not allow even the smallest foreign particles to pass through, increased strength of synthetic fibers, high-performance clothing, and increased efficiency of fuel cells.
[0003] Cellulose nanofibers are fibers with a nano-level fiber diameter of 1000 nm or less, and can be obtained by first increasing the pressure of chemically modified cellulose raw material using the high-pressure pump of a high-pressure homogenizer, and then defibrating it using mechanical shear force from the nozzle of the high-pressure homogenizer (see, for example, non-patent document 1). [Prior art documents] [Non-patent literature]
[0004] [Non-Patent Document 1] POWREX Corporation Product information https: / / www.powrex.co.jp / microfluidizer Summary of the Invention [Problem to be solved by the invention]
[0005] However, in the above-mentioned high-pressure homogenizer, extremely high pressure is repeatedly applied to the high-pressure pump, and therefore the parts of the high-pressure pump are subject to severe wear due to long-term defibration processing, resulting in the problem that expensive parts of the high-pressure pump must be replaced frequently.
[0006] An object of the present invention is to provide a cellulose nanofiber production apparatus that realizes a longer life for the high-pressure pump of the high-pressure homogenizer. [Means for solving the problem]
[0007] The present inventors have completed the present invention in order to solve the above problems. (1) A cellulose nanofiber production apparatus equipped with a high-pressure homogenizer that performs a micronization process on pulp fibers, the high-pressure homogenizer having a high-pressure pump that pressurizes a cellulose raw material that is the raw material for the cellulose nanofibers, the high-pressure pump having a cylinder that receives the cellulose raw material, a plunger that draws the cellulose raw material into the cylinder and expels it out of the cylinder by reducing and increasing the pressure inside the cylinder, an actuator that reciprocates the plunger, and a pump holder that is a positioning member for determining the relative positions of the actuator and the cylinder and is fixed to the cylinder, the cellulose nanofiber production apparatus being characterized in that a countersunk structure into which the cylinder and the pump holder fit is provided on the opposing surfaces of the cylinder and the pump holder. (2) The cellulose nanofiber production apparatus according to (1), characterized in that when the cylinder and the pump holder are engaged, the gap between the sides of the cylinder and the pump holder is 1 mm or less. (3) The cellulose nanofiber production apparatus according to (1) or (2), characterized in that the high-pressure pump further comprises a pump base fixed to the pump holder, and a countersunk structure is provided on the opposing surfaces of the pump holder and the pump base. (4) The cellulose nanofiber production apparatus according to (3), characterized in that when the pump holder and the pump base are engaged with each other, the gap between the sides of the pump holder and the pump base is 1 mm or less. Effect of the Invention
[0008] According to the present invention, it is possible to provide a cellulose nanofiber production apparatus that realizes a longer life for the high-pressure pump of the high-pressure homogenizer. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a diagram showing a schematic configuration of a high-pressure homogenizer according to an embodiment. [Diagram 2] 1 is a diagram showing a schematic configuration of a high-pressure pump according to an embodiment; [Diagram 3] 1 is a diagram showing a schematic configuration of a high-pressure pump according to an embodiment; [Figure 4] 11A and 11B are diagrams for explaining a countersunk structure for fitting a cylinder and a pump holder in the embodiment. [Diagram 5] 11A and 11B are diagrams for explaining a countersunk structure for fitting the pump holder and the pump base in the embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, a cellulose nanofiber production apparatus according to an embodiment of the present invention will be described with reference to the drawings. The cellulose nanofiber production apparatus according to this embodiment is a cellulose nanofiber production apparatus equipped with a high-pressure homogenizer that performs a micronization process on pulp fibers. FIG. 1 is a diagram showing a schematic configuration of the high-pressure homogenizer equipped in the cellulose nanofiber production apparatus according to this embodiment. The high-pressure homogenizer 1 includes a high-pressure pump 2, a nozzle unit 3, a valve 4, and pipes 5, 6, and 7. The cellulose raw material, which is the raw material for cellulose nanofibers, is transported to the high-pressure pump 2 by pipes 5 and 6. The cellulose raw material pressurized by the high-pressure pump 2 is pressure-fed to the nozzle unit 3 by pipes 6 and 7. The cellulose raw material is pressure-fed to the nozzle unit 3 in an increased pressure state, generating a strong shearing action in the nozzle unit 3, and is highly defibrated.
[0011] 2 and 3 are diagrams showing the configuration of the high-pressure pump 2 according to this embodiment, with Fig. 2 showing a state in which a plunger 10 (described later) is located at a stroke end in the downward direction of the page, and Fig. 3 showing a state in which the plunger 10 is located at a stroke end in the upward direction of the page. As described above, the high-pressure pump 2 is a pump for pressurizing the cellulose raw material, and as shown in Figs. 2 and 3, it is equipped with a cylinder 8, an outer tubular portion 9, a plunger 10, a hydraulic cylinder 11, a pump holder 14, and a pump base 15. For convenience of explanation of the configuration, the cylinder 8, the outer tubular portion 9, the pump holder 14, and the pump base 15 shown in Figs. 2 and 3 are shown in vertical central cross-sectional views, and the other configurations are shown in external views.
[0012] The cylinder 8 receives the cellulose raw material supplied through the pipe 6 shown in FIG. 1 into the cylinder. The plunger 10 has a cylindrical shape with an axis in the vertical direction of the paper surface of FIG. 2, and moves back and forth in the axial direction inside the cylinder 8. The hydraulic cylinder 11 has a piston 11a and functions as an actuator that moves the plunger 10 back and forth. When the piston 11a of the hydraulic cylinder 11 moves from the position shown in FIG. 3 to the position shown in FIG. 2, the plunger 10 moves inside the cylinder 8 from the position shown in FIG. 3 to the position shown in FIG. 2, and the cellulose raw material pumped by the pressure reducing action inside the cylinder 8 and the supply pump (not shown) is sucked into the cylinder 8. When the piston 11a of the hydraulic cylinder 11 moves from the position shown in FIG. 2 to the position shown in FIG. 3, the plunger 10 moves inside the cylinder 8 from the position shown in FIG. 2 to the position shown in FIG. 3, and the cellulose raw material is discharged outside the cylinder 8 by the pressure inside the cylinder 8. In this embodiment, the hydraulic cylinder 11 is exemplified as the actuator, but an air cylinder or a ball screw may be used.
[0013] The pump holder 14 is cylindrical and has a through hole 14d in the center through which the plunger 10 is inserted, functions as a positioning member for determining the relative positions of the hydraulic cylinder 11 and the cylinder 8, and is secured to the cylinder 8 by a securing member (not shown). Fig. 4 is an enlarged view of the inside of a circle C1 shown in Fig. 2. As shown in Fig. 4, the annular opposing surface 8a of the cylinder 8 facing the pump holder 14 has an annular convex portion, and the annular opposing surface 14a of the pump holder 14 facing the cylinder 8 has an annular concave portion, and the surfaces (opposing surfaces 8a and 14a) where the cylinder 8 and the pump holder 14 fit together are provided with a countersunk structure in which the convex portion of the opposing surface 8a and the concave portion of the opposing surface 14a fit together.
[0014] When the cylinder 8 and the pump holder 14 are fitted together, the gap G1 between the side surfaces of the cylinder 8 and the pump holder 14 (between the outer surface of the convex portion of the opposing surface 8a and the inner surface of the concave portion of the opposing surface 14a) is desirably 0.015 mm to 1 mm, more desirably 0.015 mm to 0.5 mm, and the average gap G1 in this embodiment is 0.02 mm. By providing a countersunk structure on the surfaces (opposing surfaces 8a and 14a) where the cylinder 8 and the pump holder 14 are fitted together during assembly of the high-pressure pump 2, it is possible to prevent misalignment due to play between the cylinder 8 and the pump holder 14 when the cylinder 8 and the pump holder 14 are fitted together, and to assemble the high-pressure pump 2 with the gap between the plunger 10 and the inner diameter of the cylinder 8 within an allowable range. In this embodiment, a countersunk structure is given as an example in which the opposing surface 8a of cylinder 8 is a convex portion and the opposing surface 14a of pump holder 14 is a concave portion, but the countersunk structure may also be such that the opposing surface 8a of cylinder 8 is a concave portion and the opposing surface 14a of pump holder 14 is a convex portion.
[0015] The pump base 15 has a through hole 15c in the center through which the plunger 10 is inserted, and is positioned relative to the pump holder 14 and fixed to the pump holder 14. The pump base 15 is fixed to the hydraulic cylinder 11 via a fixing member and a hydraulic cylinder head 18 (not shown). FIG. 5 is an enlarged view of the inside of a circle C2 shown in FIG. 2. As shown in FIG. 5, the annular facing surface 14f of the pump holder 14 facing the pump base 15 has a convex portion, and the annular facing surface 15a of the pump base 15 facing the pump holder 14 has a concave portion, and the surfaces (the facing surfaces 14f and 15a) where the pump holder 14 and the pump base 15 are fitted to each other are provided with a counterbore structure in which the convex portion of the facing surface 14f and the concave portion of the facing surface 15a are fitted to each other. Therefore, it is possible to prevent the pump base 15 from being misaligned with respect to the pump holder 14 when the high-pressure pump 2 is assembled.
[0016] When the pump holder 14 and the pump base 15 are fitted together, the gap G2 between the side surfaces of the pump holder 14 and the pump base 15 (between the outer surface of the convex portion of the opposing surface 14f and the inner surface of the concave portion of the opposing surface 15a) is desirably 0.015 mm to 1 mm, more desirably 0.015 mm to 0.5 mm, and the average gap G2 in this embodiment is 0.02 mm. By providing a countersunk structure on the surfaces (opposing surfaces 14f and 15a) where the pump holder 14 and the pump base 15 are fitted together during assembly of the high-pressure pump 2, it is possible to prevent misalignment due to play between the pump holder 14 and the pump base 15 when the pump holder 14 and the pump base 15 are fitted together, and to assemble the high-pressure pump 2 with the gap between the plunger 10 and the inner diameter of the cylinder 8 within an allowable range. In this embodiment, a spigot structure is given as an example in which the opposing surface 14f of the pump holder 14 is a convex portion and the opposing surface 15a of the pump base 15 is a concave portion, but the spigot structure may also be such that the opposing surface 14f of the pump holder 14 is a concave portion and the opposing surface 15a of the pump base 15 is a convex portion.
[0017] Furthermore, the pump base 15 is fixed to the pump holder 14 by a fixing member (not shown) with the opposing surface 14f of the pump holder 14 and the opposing surface 15a of the pump base 15 facing each other. In this embodiment, the pump holder 14 and the pump base 15 are formed from separate members, but the pump holder 14 and the pump base 15 may be formed from a single member.
[0018] According to the cellulose nanofiber production device of this embodiment, a countersunk structure is provided on the surface where the cylinder 8 and the pump holder 14 constituting the high-pressure pump 2 of the high-pressure homogenizer 1 are fitted together, so that misalignment due to play between the cylinder 8 and the pump holder 14 when fitting the cylinder 8 and the pump holder 14 during assembly of the high-pressure pump 2 can be prevented, and the gap between the plunger 10 and the inner diameter of the cylinder 8 can be kept within an allowable range, and the high-pressure pump 2 can be assembled. In addition, a countersunk structure is provided on the surface where the pump holder 14 and the pump base 15 constituting the high-pressure pump 2 of the high-pressure homogenizer 1 are fitted together, so that misalignment due to play between the pump holder 14 and the pump base 15 when fitting the pump holder 14 and the pump base 15 during assembly of the high-pressure pump 2 can be prevented, and the gap between the plunger 10 and the inner diameter of the cylinder 8 can be kept within an allowable range, and the high-pressure pump 2 can be assembled. Therefore, it is possible to prevent the side of the plunger 10 from hitting the inner surface of the cylinder 8 and the high-pressure seal attached to the inner surface of the cylinder 8 on the -Z direction side, so that the life of the cylinder 8 and the high-pressure seal can be extended.
[0019] (Method of manufacturing cellulose nanofiber) The production method using the cellulose nanofiber production apparatus of the present invention includes a defibration step in which a cellulose raw material is defibrated by applying a mechanical shear force with the high-pressure homogenizer 1 according to this embodiment. In the present invention, it is possible to use chemically modified cellulose as the cellulose raw material, and in that case, it is preferable to carry out a step of dehydrating and washing the dispersion of chemically modified cellulose and a step of adjusting the concentration of the dispersion of chemically modified cellulose before subjecting it to the defibration step.
[0020] (Cellulose nanofiber) Cellulose nanofibers are materials produced by finely breaking down plant fibers to the nano level, and are generally fine fibers with an average fiber diameter of about 3 to 500 nm and an average aspect ratio of 50 or more. The average fiber diameter and average fiber length of cellulose nanofibers can be obtained by averaging the fiber diameters and fiber lengths obtained from the observation of each fiber using a field emission scanning electron microscope (FE-SEM). The aspect ratio can be calculated using the following formula. Aspect ratio = average fiber length / average fiber diameter
[0021] (Cellulose raw material) In the present invention, the cellulose raw material refers to various forms of materials mainly composed of cellulose, and examples thereof include natural cellulose such as pulp (bleached or unbleached wood pulp, bleached or unbleached non-wood pulp, refined linters, pulp derived from herbs such as jute, Manila hemp, and kenaf), cellulose produced by microorganisms such as acetic acid bacteria, regenerated cellulose spun after dissolving cellulose in a solvent such as a cuprammonium solution or a morpholine derivative, and fine cellulose obtained by depolymerizing the cellulose raw material by subjecting the cellulose to hydrolysis, alkali hydrolysis, enzymatic decomposition, explosion treatment, mechanical treatment such as a vibrating ball mill, or the like.
[0022] In the present invention, when a sheet-like cellulose raw material is used, it is preferable to roughly crush it to a size of about 0.5 to 5 cm square. By roughly crushing it to the above size, the cellulose raw material can be efficiently and uniformly modified in the next reaction step. The method of roughly crushing is not particularly limited, but a single-shaft rotary shear type grinder, a double-shaft rotary shear type grinder, a multi-shaft screw type grinder, a shredder, a guillotine cutter, etc. can be used. Among these, the use of a single-shaft rotary shear type grinder is preferable from the viewpoint of rough crushing.
[0023] Cellulose has three hydroxyl groups per glucose unit and can be chemically modified in various ways. In the present invention, a cellulose raw material obtained by chemical modification (chemically modified cellulose) may be used. Examples of chemical modifications include oxidation (carboxylation), carboxymethylation, cationization, and esterification. Among these, oxidation (carboxylation) and carboxymethylation are more preferred.
[0024] (Chemical modification of cellulose) (Oxidation) In the present invention, the oxidation of the cellulose raw material can be carried out using a known method and is not particularly limited, but it is preferable to adjust the amount of carboxyl groups to 0.5 mmol / g to 3.0 mmol / g relative to the bone dry mass of the cellulose nanofiber.
[0025] As an example, cellulose can be obtained by oxidizing it in water using an oxidizing agent in the presence of an N-oxyl compound and a compound selected from the group consisting of bromides, iodides, or a mixture thereof. This oxidation reaction selectively oxidizes the primary hydroxyl group at the C6 position of the glucopyranose ring on the cellulose surface, and a cellulose-based fiber having an aldehyde group and a carboxyl group or a carboxylate group on the surface can be obtained. The concentration of cellulose during the reaction is not particularly limited, but is preferably 5% by mass or less. The N-oxyl compound refers to a compound that can generate nitroxy radicals. Any compound can be used as the N-oxyl compound as long as it promotes the desired oxidation reaction.
[0026] The amount of the N-oxyl compound used is not particularly limited as long as it is a catalytic amount capable of oxidizing the raw cellulose. For example, the amount is preferably 0.01 to 10 mmol, more preferably 0.02 to 1 mmol, and even more preferably 0.05 to 0.5 mmol per 1 g of bone dry cellulose. The amount is preferably about 0.1 to 4 mmol / L relative to the reaction system.
[0027] Bromides are compounds containing bromine, examples of which include alkali metal bromides that can dissociate and ionize in water. Also, iodides are compounds containing iodine, examples of which include alkali metal iodides. The amount of bromide or iodide used can be selected within a range that can promote the oxidation reaction. The total amount of bromide and iodide is, for example, preferably 0.1 to 100 mmol, more preferably 0.1 to 10 mmol, and even more preferably 0.5 to 5 mmol, relative to 1 g of bone-dry cellulose.
[0028] The oxidizing agent may be a known one, such as halogen, hypohalous acid, halous acid, perhalogen acid or their salts, halogen oxide, or peroxide. Among them, inexpensive sodium hypochlorite is preferred. The appropriate amount of the oxidizing agent to be used is, for example, preferably 0.5 to 500 mmol, more preferably 0.7 to 50 mmol, even more preferably 1 to 25 mmol, and most preferably 3 to 10 mmol, per 1 g of bone-dry cellulose. Also, for example, 1 to 40 mol is preferred per 1 mol of the N-oxyl compound.
[0029] The cellulose oxidation process can proceed efficiently even under relatively mild conditions. Therefore, the reaction temperature is preferably 4 to 40°C, or may be room temperature of about 15 to 30°C. As the reaction proceeds, carboxyl groups are generated in the cellulose, and a decrease in the pH of the reaction solution is observed. In order to efficiently proceed with the oxidation reaction, it is preferable to add an alkaline solution such as an aqueous sodium hydroxide solution to maintain the pH of the reaction solution at about 8 to 12, preferably 10 to 11. The reaction medium is preferably water, because it is easy to handle and does not easily cause side reactions.
[0030] The reaction time in the oxidation reaction can be appropriately set according to the degree of progress of the oxidation, and is usually about 0.5 to 6 hours, for example, about 1 to 4 hours. The oxidation reaction may be carried out in two stages. For example, the oxidized cellulose obtained by filtering after the completion of the first stage reaction is oxidized again under the same or different reaction conditions, thereby enabling efficient oxidation without reaction inhibition by table salt produced as a by-product in the first stage reaction.
[0031] Another example of the carboxylation (oxidation) method is a method in which a cellulose raw material is oxidized by contacting it with an ozone-containing gas. This oxidation reaction oxidizes at least the hydroxyl groups at positions 2 and 6 of the glucopyranose ring, and decomposes the cellulose chain. The ozone concentration in the ozone-containing gas is 50 to 250 g / m 3 It is preferable that the thickness is 70 to 220 g / m 3 It is more preferable that the ozone is added to the cellulose raw material in an amount of 0.1 to 30 parts by mass, and more preferably 5 to 30 parts by mass, based on 100 parts by mass of the solid content of the cellulose raw material. The ozone treatment temperature is preferably 0 to 50°C, and more preferably 20 to 50°C. The ozone treatment time is not particularly limited, but is about 1 to 360 minutes, and preferably about 30 to 300 minutes. When the ozone treatment conditions are within these ranges, it is possible to prevent cellulose from being excessively oxidized and decomposed, and the yield of oxidized cellulose is good. After the ozone treatment, an oxidizing agent may be used to perform a post-oxidation treatment. The oxidizing agent used in the post-oxidation treatment is not particularly limited, but examples thereof include chlorine-based compounds such as chlorine dioxide and sodium chlorite, oxygen, hydrogen peroxide, persulfuric acid, and peracetic acid. For example, these oxidizing agents are dissolved in a polar organic solvent such as water or alcohol to prepare an oxidizing agent solution, and the cellulose raw material is immersed in the solution to perform the post-oxidation treatment.
[0032] The amount of carboxyl groups, carboxylate groups, and aldehyde groups in the cellulose fiber can be adjusted by controlling the amount of oxidizing agent added and the reaction time. The amount of carboxyl groups can be measured, for example, by preparing 60 mL of a 0.5% by mass slurry (aqueous dispersion) of oxidized cellulose, adding a 0.1 M aqueous hydrochloric acid solution to adjust the pH to 2.5, then dropping a 0.05 N aqueous sodium hydroxide solution to measure the electrical conductivity until the pH reaches 11, and calculating the amount of carboxyl groups using the following formula from the amount of sodium hydroxide (a) consumed in the neutralization stage of the weak acid, where the change in electrical conductivity is gradual. Carboxyl group amount [mmol / g oxidized cellulose or cellulose nanofiber] = a (mL) x 0.05 / mass of oxidized cellulose (g)
[0033] (Carboxymethylation) In the present invention, the carboxymethylation of the cellulose raw material can be carried out using a known method, and is not particularly limited, but it is preferable to adjust the degree of carboxymethyl group substitution per anhydrous glucose unit of cellulose to 0.01 to 0.50. One example of the method is the following production method, but it may be synthesized by a conventionally known method or a commercially available product may be used. Cellulose is used as the raw material, and 3 to 20 times by mass of water and / or lower alcohol, specifically methanol, ethanol, N-propyl alcohol, isopropyl alcohol, N-butanol, isobutanol, tertiary butanol, etc., or a mixture of two or more of them is used as a solvent. The mixing ratio of the lower alcohol is 60 to 95% by mass. As the mercerizing agent, 0.5 to 20 times the moles of an alkali metal hydroxide, specifically sodium hydroxide or potassium hydroxide, per anhydrous glucose residue of the raw material is used. The starting material, solvent, and mercerizing agent are mixed, and a mercerization treatment is carried out at a reaction temperature of 0 to 70° C., preferably 10 to 60° C., for a reaction time of 15 minutes to 8 hours, preferably 30 minutes to 7 hours. Then, a carboxymethylating agent is added at 0.05 to 10.0 times the moles per glucose residue, and an etherification reaction is carried out at a reaction temperature of 30 to 90° C., preferably 40 to 80° C., for a reaction time of 30 minutes to 10 hours, preferably 1 hour to 4 hours.
[0034] The degree of carboxymethyl substitution per glucose unit can be measured, for example, by the following method. That is, 1) Weigh out about 2.0 g of carboxymethylated cellulose fiber (bone dry) and place it in a 300 mL Erlenmeyer flask with a stopper. 2) Add 100 mL of a solution of 100 mL of concentrated nitric acid in 1000 mL of nitric acid methanol, and shake for 3 hours to convert carboxymethyl cellulose salt (carboxymethylated cellulose) into hydrogenated carboxymethylated cellulose. 3) Weigh out 1.5 to 2.0 g of hydrogenated carboxymethylated cellulose (bone dry) and place it in a 300 mL Erlenmeyer flask with a stopper. 4) Wet the hydrogenated carboxymethylated cellulose with 15 mL of 80% methanol, add 100 mL of 0.1 N NaOH, and shake at room temperature for 3 hours. 5) Using phenolphthalein as an indicator, back-titrate the excess NaOH with 0.1 N H2SO4. 6) Calculate the degree of carboxymethyl substitution (DS) by the following formula. A = [(100 × F'-(0.1N H2SO4) (mL) × F) × 0.1] / (bone-dry mass of hydrogenated carboxylated cellulose (g)) DS = 0.162 x A / (1-0.058 x A) A: The amount of 1N NaOH required to neutralize 1 g of hydrogenated carboxymethyl cellulose (mL) F': Factor of 0.1N H2SO4 F: Factor of 0.1N NaOH
[0035] (cationization) In the present invention, the cationization of the cellulose raw material can be carried out using a known method, and the cationization can result in the cellulose molecule having, for example, ammonium, phosphonium, sulfonium, or a group having these ammonium, phosphonium, or sulfonium, but a group having ammonium is preferred, and a group containing quaternary ammonium is particularly preferred. The specific cationization method is not particularly limited, but as an example, a cationization agent such as glycidyl trimethyl ammonium chloride, 3-chloro-2 hydroxypropyl trialkyl ammonium hydride, or a halohydrin type thereof, and an alkali metal hydroxide (sodium hydroxide, potassium hydroxide, etc.) as a catalyst can be reacted with the cellulose raw material in the presence of water and / or an alcohol having 1 to 4 carbon atoms to obtain a cationically modified cellulose having a group containing quaternary ammonium.
[0036] In this method, the degree of cationic substitution per glucose unit of the cationically modified cellulose obtained can be adjusted by controlling the amount of the cationizing agent to be reacted and the composition ratio of water and / or alcohol having 1 to 4 carbon atoms. The degree of substitution here refers to the number of substituents introduced per unit structure (glucopyranose ring) constituting cellulose. In other words, it is defined as "the value obtained by dividing the number of moles of the introduced substituents by the total number of moles of hydroxyl groups in the glucopyranose ring." Pure cellulose has three substitutable hydroxyl groups per unit structure (glucopyranose ring), so the theoretical maximum value of the degree of substitution of the cellulose fiber of the present invention is 3 (the minimum value is 0).
[0037] In the present invention, the cationic substitution degree per glucose unit of the cationized cellulose is preferably 0.01 to 0.40. By introducing cationic substituents into cellulose, the celluloses are electrically repelled from each other. Therefore, cellulose into which cationic substituents have been introduced can be easily nanofibrillated. If the cationic substitution degree per glucose unit is less than 0.01, sufficient nanofibrillation cannot be achieved. On the other hand, if the cationic substitution degree per glucose unit is more than 0.40, the cellulose may swell or dissolve, making it impossible to maintain the fiber form, and may not be obtained as nanofibers.
[0038] The degree of cationic substitution per glucose unit can be calculated by the following formula after drying the sample (cationically modified cellulose) and measuring the nitrogen content with a total nitrogen analyzer TN-10 (Mitsubishi Chemical). The degree of substitution here refers to the average value of the number of moles of substituents per mole of anhydrous glucose unit. Degree of cation substitution = (162 x N) / (1-151.6 x N) N: Nitrogen content
[0039] (Esterification) The method for esterifying a cellulose raw material or defibrated cellulose fibers to obtain esterified cellulose fibers or esterified cellulose nanofibers is not particularly limited, but an example of the method is to react the cellulose raw material or defibrated cellulose fibers with compound A. Compound A will be described later.
[0040] Examples of methods for reacting compound A with the cellulose raw material or defibrated cellulose fibers include a method of mixing a powder or an aqueous solution of compound A with the cellulose raw material or defibrated cellulose fibers, a method of adding an aqueous solution of compound A to a slurry of the cellulose raw material or defibrated cellulose fibers, etc. Of these, the method of mixing an aqueous solution of compound A with the cellulose raw material or defibrated cellulose fibers or a slurry thereof is preferred because it increases the uniformity of the reaction and increases the efficiency of esterification.
[0041] Examples of compound A include phosphoric acid compounds (e.g., phosphoric acid, polyphosphoric acid), phosphorous acid, phosphonic acid, polyphosphonic acid, and esters thereof. Compound A may be in the form of a salt. Among the above, phosphoric acid compounds are preferred because they are low cost, easy to handle, and can be introduced into cellulose of a cellulose raw material (e.g., pulp fiber) to improve defibration efficiency. The phosphoric acid compound may be any compound having a phosphoric acid group, and examples thereof include phosphoric acid, sodium dihydrogen phosphate, disodium hydrogen phosphate, trisodium phosphate, sodium pyrophosphate, sodium metaphosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, tripotassium phosphate, potassium pyrophosphate, potassium metaphosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, triammonium phosphate, ammonium pyrophosphate, and ammonium metaphosphate. The phosphoric acid compounds used may be one type or a combination of two or more types. Among these, from the viewpoints of high efficiency of introduction of phosphate groups, ease of defibration in the defibration step described below, and ease of industrial application, phosphoric acid, sodium salts of phosphoric acid, potassium salts of phosphoric acid, and ammonium salts of phosphoric acid are preferred, sodium salts of phosphoric acid are more preferred, and sodium dihydrogen phosphate and disodium hydrogen phosphate are even more preferred. In addition, it is preferable to use an aqueous solution of a phosphoric acid compound in the esterification, since this increases the uniformity of the reaction and the efficiency of introduction of the phosphate group. The pH of the aqueous solution of the phosphoric acid compound is preferably 7 or less, since this increases the efficiency of introduction of the phosphate group. A pH of 3 to 7 is more preferred from the viewpoint of suppressing hydrolysis of the pulp fibers.
[0042] Examples of the esterification method include the following methods. Compound A is added to a suspension (for example, solid content concentration 0.1 to 10% by mass) of cellulose raw material or defibrated cellulose fiber while stirring to introduce phosphate groups into cellulose. When the cellulose raw material or defibrated cellulose fiber is 100 parts by mass, and compound A is a phosphoric acid compound, the amount of compound A added is preferably 0.2 parts by mass or more, more preferably 1 part by mass or more, in terms of phosphorus element amount. This can further improve the yield of esterified cellulose fiber or esterified cellulose nanofiber. The upper limit is preferably 500 parts by mass or less, more preferably 400 parts by mass or less. This can efficiently obtain a yield commensurate with the amount of compound A used. Therefore, 0.2 to 500 parts by mass is preferable, and 1 to 400 parts by mass is more preferable.
[0043] When compound A is reacted with the cellulose raw material or defibrated cellulose fibers, compound B may also be added to the reaction system. Examples of methods for adding compound B to the reaction system include adding compound B to a slurry of the cellulose raw material or defibrated cellulose fibers, an aqueous solution of compound A, or a slurry of the cellulose raw material or defibrated cellulose fibers and compound A.
[0044] Compound B is not particularly limited, but is preferably a basic compound, and is more preferably a nitrogen-containing compound that is basic. "Basic" usually means that an aqueous solution of compound B exhibits pink to red color in the presence of a phenolphthalein indicator, and / or that the pH of the aqueous solution of compound B is greater than 7. The nitrogen-containing compound that is basic is not particularly limited as long as it exhibits the effects of the present invention, but is preferably a compound having an amino group. Examples of compounds having an amino group include urea, methylamine, ethylamine, trimethylamine, triethylamine, monoethanolamine, diethanolamine, triethanolamine, pyridine, ethylenediamine, and hexamethylenediamine. Among these, urea is preferred because of its low cost and ease of handling. The amount of compound B added is preferably 2 to 1000 parts by mass, more preferably 100 to 700 parts by mass. The reaction temperature is preferably 0 to 95°C, more preferably 30 to 90°C. The reaction time is not particularly limited, but is usually about 1 to 600 minutes, and is preferably 30 to 480 minutes. When the esterification reaction conditions are within any of these ranges, it is possible to prevent the cellulose from being excessively esterified and becoming easily soluble, and it is possible to improve the yield of phosphated cellulose.
[0045] After reacting the cellulose raw material or defibrated cellulose fibers with compound A, a suspension of esterified cellulose fibers or esterified cellulose nanofibers is usually obtained. The suspension of esterified cellulose fibers or esterified cellulose nanofibers is dehydrated as necessary. It is preferable to carry out a heat treatment after dehydration. This can suppress hydrolysis of the cellulose raw material or defibrated cellulose fibers. The heating temperature is preferably 100 to 170°C, and it is more preferable to heat at 130°C or less (more preferably 110°C or less) while water is contained during the heat treatment, and then heat at 100 to 170°C after removing the water.
[0046] In cellulose phosphate, a phosphate group substituent is introduced into cellulose, and cellulose particles repel each other electrically. Therefore, cellulose phosphate fibers can be easily defibrated to cellulose nanofibers (defibration performed to obtain cellulose nanofibers is also called nanofibrillation). The degree of phosphate group substitution per glucose unit of cellulose phosphate fibers is preferably 0.001 or more. This allows sufficient defibration (e.g. nanofibrillation) to be performed. The upper limit of the degree of phosphate group substitution per glucose unit of cellulose phosphate fibers is preferably 0.40 or less. This can suppress swelling or dissolution of cellulose phosphate fibers, and can suppress the occurrence of a situation in which cellulose nanofibers cannot be obtained. Therefore, the degree of phosphate group substitution per glucose unit of cellulose phosphate fibers is preferably 0.001 to 0.40. In addition, the degree of phosphate group substitution per glucose unit of cellulose nanofibers modified by phosphate esterification (phosphated cellulose nanofibers) is preferably 0.001 or more. The upper limit is preferably 0.40 or less. Therefore, the degree of phosphate substitution per glucose unit of the phosphated cellulose nanofiber is preferably 0.001 to 0.40. It is preferable that the phosphated cellulose fiber is subjected to a washing treatment such as boiling and then washing with cold water. This allows efficient defibration.
[0047] The reaction tank used in the process of chemically modifying the cellulose raw material to obtain modified cellulose is not particularly limited, but examples include a tank equipped with stirring blades, a pulper, a kneader, a ribbon-type mixer, a screw-type mixer, etc. Among these, when the reaction is carried out at a raw material concentration of approximately 3% or less, it is preferable to use a tank or a pulper equipped with stirring blades that can stir liquids or liquid-like slurries. Furthermore, when the reaction is carried out under conditions where the raw material concentration exceeds approximately 3%, since the reactants are not in a liquid form but are solid, it is preferable to use a kneader, ribbon-type mixer, or screw-type mixer that can mix and stir them.
[0048] (Cleaning process) In the present invention, the obtained dispersion of chemically modified cellulose is subjected to a dehydration treatment and then washed with water, and this process makes it possible to obtain cellulose nanofibers with few impurities.
[0049] In this step, dehydration devices of the centrifugal separation type, vacuum dehydration type, and pressure dehydration type can be used. Specifically, centrifugal separation type (Tanabe Willtec centrifuge, Kokusan centrifuge, etc.), vacuum dehydration type (drum type vacuum dehydrator, Tsukishima Kikai horizontal belt filter, pressure dehydration type (filter press, tube press), screw press, belt press horizontal belt filter, polydisc filter, vibration screen, etc. can be mentioned. Among these, pressure dehydration type (filter press, tube press), centrifugal separation type (Tanabe Willtec centrifuge, Kokusan centrifuge, etc.), and vacuum dehydration type (drum type vacuum dehydrator) are preferred because they can perform dehydration without applying strong shear force to the dehydrated raw material. In addition, a combination of these types can also be used.
[0050] (Concentration adjustment process for chemically modified cellulose) In the present invention, in order to efficiently carry out the subsequent defibration step, it is preferable to adjust the concentration of the dispersion of chemically modified cellulose to 0.1% by mass to 10% by mass. If the concentration is less than 0.1% by mass, the presence of too little modified pulp will result in insufficient defibration. On the other hand, if the concentration exceeds 10% by mass, the viscosity of the modified pulp dispersion increases as defibration proceeds, making it impossible to apply sufficient force to the modified pulp, resulting in insufficient defibration.
[0051] (defibration process) In the present invention, the high-pressure homogenizer 1 according to this embodiment is used to defibrate chemically modified cellulose. Defibration using the high-pressure homogenizer 1 is performed by applying a pressure of 50 MPa or more and a strong shear force to the aqueous dispersion. The applied pressure is more preferably 100 MPa or more, and even more preferably 140 MPa or more. Furthermore, prior to defibration and dispersion treatment using the high-pressure homogenizer 1, it is also possible to subject the above-mentioned cellulose nanofibers to a preliminary treatment, if necessary, using a known mixing, stirring, emulsifying, or dispersing device such as a high-speed shear mixer.
[0052] When defibrating by the above treatment, the solids concentration of the cellulose fiber raw material is 0.1% by mass or more, preferably 0.2% by mass or more, particularly 0.3% by mass or more, and 10% by mass or less, particularly 6% by mass or less. If the solids concentration is too low, the amount of liquid will be too large for the amount of cellulose fiber raw material to be treated, resulting in poor efficiency, and if the solids concentration is too high, the fluidity will be poor. [Explanation of symbols]
[0053] 1...high-pressure homogenizer, 2...high-pressure pump, 3...nozzle portion, 4...valve, 5, 6, 7...piping, 8...cylinder, 10...plunger, 11...hydraulic cylinder, 11a...piston, 14...pump holder, 15...pump base, 18...hydraulic cylinder head.
Claims
1. A cellulose nanofiber production apparatus equipped with a high-pressure homogenizer for finely pulp fiber processing, The high-pressure homogenizer is equipped with a high-pressure pump that pressurizes the cellulose raw material that is the raw material for the cellulose nanofibers, The high pressure pump is a cylinder for receiving the cellulose feedstock; A plunger that draws the cellulose raw material into the cylinder and expels it out of the cylinder by reducing and increasing the pressure inside the cylinder; An actuator that reciprocates the plunger; a pump holder fixed to the cylinder for determining a relative position of the actuator and the cylinder; A cellulose nanofiber production apparatus, characterized in that a countersunk structure into which the cylinder and the pump holder fit is provided on the opposing surfaces of the cylinder and the pump holder.
2. The cellulose nanofiber production apparatus according to claim 1, characterized in that a gap between the side surfaces of the cylinder and the pump holder when the cylinder and the pump holder are engaged is 1 mm or less.
3. The high pressure pump is a pump base fixed to the pump holder; The cellulose nanofiber production device according to claim 1 or 2, characterized in that a countersunk structure is provided on the opposing surfaces of the pump holder and the pump base.
4. The cellulose nanofiber production apparatus according to claim 3, characterized in that a gap between the side surfaces of the pump holder and the pump base when the pump holder and the pump base are fitted together is 1 mm or less.
Citation Information
Patent Citations
Pump
JP2015218630A
Organic solvent dispersion method of cellulose nanofiber and apparatus of the same
JP2020183483A
Cellulose nanofiber composition and production method therefor
JP2022102007A
Piston pump
KR1020200129061A